国际商事仲裁费用构成及合理控制仲裁费用探索 - 侯, 进才 (Journal of Oil and Gas Technology, 2021)
仲裁作为解决国际商事争议的主要方式之一，受到国际工程承包企业的青睐，然而当事人在决定一个案件是否要提起仲裁时，常会把仲裁费用作为一个重要考量指标，高昂的仲裁费用可能会限制国际商事仲裁制度的健康发展。本文以2017版国际商会仲裁规则下的收费标准为基础，从仲裁费用的构成、计算方法入手，探讨了仲裁费用影响因素，并给出了控制仲裁过程费用的合理化建议。 Arbitration, as one of the main ways to resolve international commercial disputes, remains a popular choice for international engineering company. The arbitration fees will be an important evaluating indicator when the parties considering apply for arbitration. Expensive arbitration fees may restrict the healthy development of international commercial arbitration system. Based on the arbitration cost and fees under the arbitration rules of the 2017 edition of the International Chamber of Commerce, characteristics, composition and calculation method of the arbitration fees are showed in this paper firstly; then, its influencing factors are discussed. Reasonable suggestions for controlling the arbitration fees are given in the end of this paper.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Fees; Composition of Arbitration Fees; Controlling the Arbitration Fees; International Commercial Disputes; 仲裁费用; 国际商事; 控制费用; 费用构成